Descending necrotizing mediastinitis secondary to periodontal infection. Case report and review - Intriago, Jaime; Arriciaga, Johana; Macías, Rocío; Arcos, Tania (Revista Universidad de Guayaquil, 2010)
Descending necrotizing mediastinitis is an acute disease with high mortality. It is a primary complication of cervical or dental infection that spreads to the mediastinum under through facial anatomical spaces, in some cases this complication is secondary to the spread of infection from other sites or trauma, the causes are grouped into 4 categories: esophageal perforation, infection of head and neck infection originated elsewhere and cardiothoracic surgery. The most common causein our population is the dental followed by upper respiratory tract infections. Currently improved treatment and reduced mortality, due to the understanding of its pathophysiology and anatomical areas involved, but depends on the diagnosis and treatment against orocervical infectious processesin the new preventive dental care system should not exist in theory but neglect the patient, benignlesions may be complicated by fatal injuries. A patiente of the Sistema Hospitalario Docente de la Universidad De Guayaquil will be presented.